PERAN ROH KUDUS DALAM SAKRAMEN KRISMA, PENGURAPAN ORANG SAKIT DAN IMAMAT - Yanto, Stepanus Yedi; Firmanto, Antonius Denny; Aluwesia, Nanik Wijiyati (Pastoralia Jurnal Penelitian Dosen, 2023)
Sacraments  are  signs  given  by  Jesus  to  His  people.  Through  the  sacraments,  humans  are reunited with God. In Catholicism there are seven sacraments. Each sacrament has different graces  and  meanings.  In  this  research,  the  author  used  descriptive  qualitative  research methods  using  data  analysis.  In  qualitative  research  methods,  the  subject's  perspective  is emphasized more. The author analyzes these data through literature study. The result of this research  is  that  through  the  sacrament  of  chrismation,  our  relationship  with  the  Church  is increasingly  perfected  because  of  the  special  power  of  the  Holy  Spirit.  The  grace  of  the sacrament  of  anointing  of  the  sick  makes  the  sick  person  strengthened  and  united  with  the suffering  of  Jesus  Christ.  Through  the  grace  of  the  sacrament  of  priesthood,  the  Hierarchs have the special power topresent the body and blood of Christ in the celebration of the holy eucharist.